Migratory movements of British and Irish Common Shelduck Tadorna tadorna: a review of ringing data and a pilot tracking study to inform potential interactions with offshore wind farms in the North Sea. Issue 2 (3rd July 2019) - Green, Ros M.W.; Burton, Niall H.K.; Cook, Aonghais S.C.P.
ABSTRACT: Offshore wind farms are a key part of the UK government strategy to reduce carbon emissions and mitigate climate-change impacts; however, it is important to understand their potential impacts on wildlife. The majority of British and Irish Common Shelduck Tadorna tadorna undergo a moult migration to the Wadden Sea, passing wind farms in the southern North Sea en route. We conducted a review of ring-recovery data from the British and Irish Ringing Scheme and a pilot tracking study to inform understanding of migration routes. Analysis of recovery data confirmed that British and Irish Shelduck occurred in the Wadden Sea predominantly between August and November, and use moulting sites in the Dutch Wadden Sea and Helgoland Bight. Four Shelduck were successfully tracked from East Anglia to the Wadden Sea. Four separate routes across the North Sea were identified, with previously unreported stopovers noted in the Dutch Wadden Sea, before birds continued on to moult sites in the Helgoland Bight. Flight speeds of 30.3 ± 9.2 knots (n = 299, range 8.7–55.0 knots) were recorded, and altitudes of up to 354 m. An expansion to the tracking study is planned, to increase sample sizes and geographical representation.